Beyond boundaries: exploring the role of extracellular vesicles in organ-specific metastasis in solid tumors - Nidhi, Goutham; Yadav, Vikas; Singh, Tejveer; Sharma, Deepika; Bohot, Monica; Satapathy, Shakti Ranjan (Frontiers in Immunology, 2025)
Extracellular vesicles (EVs) have been identified as important mediators of cancer metastasis, especially in the establishment of organ-specific metastatic niches. These membranous vesicles secreted by tumor cells release diverse bioactive cargo, including proteins, nucleic acids, and lipids, thereby allowing for intercellular communication and microenvironment modulation. Recent evidence demonstrates that EVs can also contribute to the formation of pre-metastatic niches by reprogramming immune cells, modifying the stromal environment, and inducing epithelial-mesenchymal transition (EMT) to promote metastatic colonization. In this review, we describe the molecular mechanism of organotropic metastasis orchestrated by EVs, with special emphasis on immune modulation and tumor microenvironment reprogramming. We also explore the potential of EVs as biomarkers for early detection of metastasis and as potential therapeutic targets for combating metastatic progression. Dissociating EV species and their influence on tumor dissemination will undoubtedly pave the way for implementing novel anti-cancer strategies to intercept tumor dissemination at its very early stages.